Evaluating the Socioeconomic and Environmental Factors of Out-migration in Aguata Local Government Area of Anambra State - Perpetua , Ogamba, Ukamaka; Chukwukalo , Ezeomedo, Innocent (African Journal of Education,Science and Technology (AJEST), 2016)
Out-migration resulting from environmental degradation and socioeconomic factors are key processes of rural population redistribution in the developing world. However studies that integrate socioeconomic and environmental factors in the study of rural out-migration are lacking in literature. This study therefore used survey data, to investigate the combined influence of socioeconomic and environmental factors on rural out-migration in Aguata Local Government Area, Nigeria. In achieving this, the study examined the characteristics of rural out-migrants and ascertained human and physical environmental factors, which influence rural out-migration in the study area. Descriptive statistics is used to explain pattern of rural out-migration in the study area. Given the mix of myriads of socioeconomic and environmental factors that drive migration, Principal Component Analysis (PCA) is used to identify the underlying dimensions of these migration determinants. The result of the findings show that migration stream is high among the youths and young adults of age range 18-37, mostly to places of commercial and educational activities. The factors that predominate in influencing their out-migration are insecurity, scarcity of food as a result of insufficient means of livelihood and erosion problem, which can be attributed to social, economic and physical environmental factors respectively. It was however recommended that social sector in government should establish human development centres in the study area, where youths who want to learn skills will be empowered, so that they will be able to establish a sustainable means of livelihood in their rural origin areas, among others